Team vs. individual sports in adolescence: gendered mechanisms linking emotion regulation, social support, and self-efficacy to psychological resilience - Wei, Dongyue; Xue, Jiajie; Sun, Bingbing (Frontiers in Psychology, 2025)
ObjectiveThis study advances current understanding by systematically investigating how team vs. individual sports differentially influence adolescent psychological resilience through emotion regulation, social support, and self-efficacy pathways, with particular attention to gender moderation effects.MethodsDrawing on multi-wave data from 698 Chinese adolescents (aged 12–18 years), we implemented a mediation model featuring two distinct pathways to elucidate mechanisms unique to each sport type. Hierarchical regression and bootstrapped analyses were utilized to evaluate: (1) the unique mediating contributions of emotion regulation (ER), social support (SS), and self-efficacy (SE) across sport categories, and (2) the moderating influence of gender on these pathways.Results(1) Team sports significantly enhance adolescents' levels of social support while individual sports notably improve self-efficacy; both types of exercise positively predict psychological resilience. (2) Emotional regulation, social support, and self-efficacy play significant mediating roles between physical activity and psychological resilience. Specifically, team sports primarily influence psychological resilience by enhancing social support and subsequently boosting self-efficacy; conversely, individual sports mainly strengthen psychological resilience through increased self-efficacy. (3) Gender has a significant moderating effect within team sports; specifically, Female exhibit a stronger impact of emotional regulation on psychological resilience compared to male who demonstrate more pronounced benefits from enhanced self-efficacy regarding their psychological resilience. In contrast to team sports, gender significantly moderated the social support-resilience relationship in individual sports, with stronger associations observed for female.ConclusionOur findings demonstrate that sport types function as gendered ecological niches for resilience cultivation. Specifically, team settings leverage interpersonal dynamics to enhance male self-efficacy and Female emotional competencies, while individual activities offer equitable platforms for social support development. These insights contest uniform exercise recommendations and furnish a blueprint for tailored, gender-sensitive interventions grounded in sport participation.